Crop species transferability of G-SSR and EST-SSR markers to Neltuma affinis spreng - Soldati, Maria Cristina; Gavier Pizarro, Gregorio Ignacio; Morales, Matias; Pomponio, Maria Florencia; Zelener, Noga (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria (España), 2024)
Aim of study: To examine the transferability of G-SSR (genomic simple sequence repeats) and EST-SSR (expressed sequence tag simple sequence repeats) markers developed for several Neltuma species to N. affinis, a species with no genomic data. Area of study: West-Center of Entre Ríos province, Argentina. The set of molecular markers here proposed can be used to analyze samples from the entire species’ distribution range. Material and methods: Twenty-five genomic G-SSRs and eleven EST-SSRs from multiple species were amplified in thirty N. affinis genotypes. Polymorphism, discrimination power and possible deviations from Hardy-Weinberg equilibrium were assessed. Main results: Seventeen highly polymorphic G-SSRs were successfully transferred to N. affinis, with a PIC (polymorphic information content) average value of 0.811 and a He (expected heterozygosity) average value of 0.694; thirteen were validated, showing very low frequencies of null alleles and no linkage disequilibrium. Additionally, seven polymorphic EST-SSRs were transferred. As expected, PIC and He average values were low. Six out of seven markers were validated, and very low frequencies of null alleles and no linkage disequilibrium were observed. Research highlights: This work provides information on the levels of microsatellites’ cross transferability to N. affinis, and its polymorphism degree. Two sets of polymorphic SSRs (genomic and expressed) to study the genetic status of the species are proposed.